ISSUES OF WOMEN’S EDUCATION IN NAXAL AFFECTED AREAS OF BIHAR - singh, Nisha (Innovative Research Thoughts, 2017)
Education has always been a foundation for economic and social development and it will be essential for the knowledge economies of the 21st century. Education manifests itself in many ways like cognitive thinking, affirmative thought system etc. It brings well-being to the society. Education of women is vital not only on grounds of social justice but also because it accelerates social transformation. Level of literacy and educational attainment are important indicators of development of any given society and we cannot exclude rural women in the development of any society as they equally contribute to the progress of the society and largely to the economy. The last decade in Bihar (2004-14) has seen an exceptional development in education. Efforts by the Government of Bihar to increase accessibility to educational facilities in the state are showing signs of positive change.